2007
DOI: 10.1259/bjr/97270791
|View full text |Cite
|
Sign up to set email alerts
|

Posterior mediastinal dumbbell ganglioneuroma with fatty replacement

Abstract: We report a case of a posterior mediastinal dumbbell ganglioneuroma with fatty replacement on CT and MRI. Most dumbbell tumours are neurogenic in origin. Fatty replacement of non-lipomatous malignancies is rare. This report suggests that a ganglioneuroma with fatty replacement should be added to the differential diagnosis of fat-containing posterior mediastinal tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…Some researchers regard adipose tissue in the posterior mediastinal lesion as a characteristic feature for diagnosis of ganglioneuroma [9,11,13]. Only two cases in our study showed adipose tissue, and they were misdiagnosed pre-operatively due to lack of knowledge.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Some researchers regard adipose tissue in the posterior mediastinal lesion as a characteristic feature for diagnosis of ganglioneuroma [9,11,13]. Only two cases in our study showed adipose tissue, and they were misdiagnosed pre-operatively due to lack of knowledge.…”
Section: Discussionmentioning
confidence: 57%
“…Thoracic ganglioneuroma needs to be differentiated from other tumours [8,13,15,16]. Cystic teratoma is round with multiple cavities, as well as calcification in the cystic wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9] Ganglioneuromas are derived from the primordial neural crest cells that form the sympathetic nervous system and are composed of a combination of mature ganglion cells and other mature tissues. Ganglioneuromas are most commonly located in the posterior mediastinum, followed by the retroperitoneum and adrenal gland.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the characteristics of their internal structures, calcifications are often seen and they predominantly exhibit low to intermediate signal intensity on CT. [3][4][5] Previous studies have reported that some ganglioneuromas display a whorled appearance caused by curvilinear internal structures or fatty components, which are detected in approximately half and one-third of cases, respectively. 4,6,7 Schwannomas are encapsulated spherical masses that are mainly found in the posterior mediastinum. However, they sometimes grow through the intervertebral foramina and form dumbbell-shaped lesions.…”
Section: Discussionmentioning
confidence: 99%